Rebelling against relevance: how to find what we want and not what Google thinks we want - Merlo-Vega, José-Antonio (Anuario ThinkEPI, 2012)
Google is a tool for retrieving high-value information, but its growing adaptation of search results to commercial criteria, based on an alleged adaptation to user preferences of the links offered, presents some problems. Now it is neccessary to filter the information, to use operators or to modify the queries in order to obtain the desired results. Some tips are offered for information professionals who want to rebel against the false concept of relevance and find what we´re looking for.